Pengukuran Keserupaan pada Communication Diagram menggunakan Metode Graph Edit Distance - Munawaroh, Hidayatul (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
E-learning is an electronic learning system that is created as a learning media so that the delivery of learning material and assessment of answers to practice questions and exams can be done online. Learning with e-learning method provides opportunities for students to take part in learning at flexible locations and times. The e-learning model is widely used in learning, so it is necessary to increase the need to automate the evaluation process in e-learning. In practice, some learning topics include descriptive answers or pictures in the form of Unified Modeling Language (UML) diagrams such as exam questions on Software Requirements Engineering (SRE). So it is necessary to develop an answer evaluation method in the form of a UML diagram. This study uses graph modeling on communication diagrams to measure the similarity between two diagrams and measure the similarity between two communication diagrams. After doing graph modeling, then its similarity is measured using the Graph Edit Distance method. From the results of this study it is proven that the similarity of communication diagrams can be measured by the Graph Edit Distance method by modeling the diagram into the previous graph form.